Emerging Translational Research in Neurological and Psychiatric Diseases: From In Vitro to In Vivo Models - Tanaka, Masaru; Giménez-Llort, Lydia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Translational research is required to uncover the underlying pathomechanisms of neurological and psychiatric disorders, search for new biomarkers, and develop novel therapeutics. Complex polygenic, multifactorial, and heterogeneous mechanisms have been elucidated using in vivo and in vitro models. Advanced preclinical models have recently revealed an intriguing interaction between sex/gender and aging in the pathogenesis and clinical manifestations of neuropsychiatric disorders. Despite these advances, much work remains to be carried out to fully understand the underlying pathology of these conditions and to develop treatments that can significantly improve the lives of those who suffer from them. The current challenge in the field of neurological and psychiatric disorders is the development of disease-modifying, effective treatments for these complex and long-term debilitating conditions with a high malady burden. The first edition of this research topic, entitled 'Emerging Translational Research in Neurological and Psychiatric Diseases: From In Vitro to In Vivo Models,' emphasizes the importance of translational research in bridging the gap between basic research and clinical applications. Furthermore, it provided a venue for researchers to share their findings and progress in translational research in this field.